Topiramate-associated acute, bilateral, angle-closure glaucoma: case report - Lucas Barasnevicius Quagliato (Arquivos Brasileiros de Oftalmologia, 2013)
This paper describes a topiramate induced acute bilateral angle-closure glaucoma. This rare adverse effect is an idiosyncratic reaction characterized by uveal effusion and lens forward displacement, leading to increased intraocular pressure and vision loss. We describe a 55 year-old white woman with migraine, spasmodic torticollis and essential tremor, who developed bilateral acute angle-closure glaucoma, one week after starting topiramate 25 mg/day. She was seen at the Ophthalmology Emergency Department of the Fundação João Penido Burnier (Campinas, SP, Brazil) with a 4 hours history of blurry vision, ocular pain and bright flashes vision. Slit lamp examination revealed moderate conjunctival injection and corneal edema, and shallow anterior chambers. Intraocular pressure was 48 mmHg in both eyes. Fundoscopic examination findings were normal. She was treated with timolol, brimonidine, dorzolamide, pilocarpine, prednisone acetate eye drops and acetazolamide. One hour after those measures, as the intraocular pressure was 30 mmHg, she received a manitol intravenous injection and the intraocular pressure normalized. After 24 hours an iridotomy with Yag laser was performed. Topiramate was discontinued and she was totally recovered after one week.